Efficacy and Safety of a Dexamethasone Implant in Patients with Diabetic Macular Edema at Tertiary Centers in Korea. (17th May 2016) - Moon, Byung Gil; Lee, Joo Yong; Yu, Hyeong Gon; Song, Ji Hun; Park, Young-Hoon; Kim, Hyun Woong; Ji, Yong-Sok; Chang, Woohyok; Lee, Joo Eun; Oh, Jaeryung; Chung, Inyoung
Abstract : Purpose . To evaluate the real-world efficacy and safety of the dexamethasone implant (DEX implant) in patients with diabetic macular edema (DME). Methods . Retrospective, multicenter, and noncomparative study of DME patients who were treated with at least one DEX implant. A total of 186 eyes from 165 patients were included. Best-corrected visual acuity (BCVA), central retinal thickness (CRT), complications, and number of retreatments were collected. Data at baseline and monthly for 6 months were analyzed. Results. The average baseline BCVA and CRT were 0.60 LogMAR and 491.6 μ m, respectively. The mean BCVA improved until 3 months and then decreased up to 6 months of follow-up (0.53, 0.49, and 0.55 LogMAR at 1, 3, and 6 months;p = 0.001, <0.001, and 0.044, resp.). The change of mean CRT was similar to BCVA (345.0, 357.7, and 412.5 μ m at 1, 3, and 6 months, p < 0.001, <0.001, and <0.001, resp.). 91 eyes (48.9%) received additional treatment with anti-VEGF or DEX implant. The average treatment-free interval was 4.4 months. In group analyses, the DEX implant was more effective in pseudophakic eyes, DME with subretinal fluid (SRF), or diffuse type. Conclusions. Intravitreal dexamethasone implants are an effective treatment for patients with DME, most notably in pseudophakic eyes, DME with SRF, or diffuse type. A half of these patients require additional treatment within 6 months.